Predicting Seedling Emergence of Three Canarygrass (Phalaris) Species under Semi-Arid Conditions Using Parametric and Non-Parametric Models - Carlos Sousa-Ortega; Aritz Royo-Esnal; José María Urbano (Agronomy, 2021)
The Phalaris genus includes annual weed species such as short-spiked canarygrass (Phalaris brachystachys Link.), little-seed canarygrass (Phalaris minor Retz.) and hood canarygrass (Phalaris paradoxa L.), which are especially problematic in Spain; as such, there is a need to develop models to predict the timing of their emergence. Field experiments were conducted at two different locations during two (2006/07 and 2007/08) and three (from 2005/06 to 2007/08) growing seasons. In both locations, 500 seeds of each Phalaris species were sown each growing season, simulating rain-fed cereal field conditions. In addition, the models were validated with three, four and eight independent experiments for P. brachystachys, P. minor and P. paradoxa, respectively. The emergence period of the three Phalaris species lasted between 31 and 48 days after sowing (DAS), showing two main flushes. The three cardinal points for parametric and non-parametric models were established to be between −1 °C and 1 °C for base temperature, between 9.8 °C and 11.8 °C for optimal temperature and between 21.2 °C and 23.4 °C for ceiling temperature; base water potential was estimated to be between −1 and −1.1 MPa. Both parametric and non-parametric models obtained similar results and were successfully validated in 12 out of 15 independent experiments.